Transformation between polar and rectangular coordinates of stiffness and dampness parameters in hydrodynamic journal bearings - Zhuxin Tian; Yu Huang (Friction)
Abstract The stiffness and dampness parameters of journal bearings are required in rectangular coordinates for analyzing the stability boundary and threshold speed of oil film bearings. On solving the Reynolds equation, the oil film force is always obtained in polar coordinates; thus, the stiffness and dampness parameters can be easily obtained in polar coordinates. Therefore, the transformation between the polar and rectangular coordinates of journal bearing stiffness and dampness parameters is discussed in this study.